PERENCANAAN EMBUNG TAMANREJO KECAMATAN SUKOREJO, KABUPATEN KENDAL - Arvie Narayana; Bachtiar Khoirom W.; Abdul Kadir; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Residents in the village Tamanrejo, District Sukorejo, Kendal in general to work as farmers who rely on irrigation water requirements of Kajar river to irrigate the fields. But it is not uncommon for residents of the village Tamanrejo crop failures due to river discharge Kajar can not meet the needs of irrigation water. To overcome this building constructed in the form of reservoir water. Extensive watershed of Embung Tamanrejo is 12,88 km2 . Embung Tamanrejo planned to meet the needs of irrigation water in the District Sukorejo, irrigation area that will be served an area of 750 hectares. Determination of dimensions Embung Tamanrejo using flood discharge plan of HSS Gama first method of 83,189 m3 / sec with a return period of 50 years. Debit mainstay Kajar River is calculated based on the method of water balance. In August to November there is a shortage of water at 95.822,61 m3. Small Dam volume of 162.636,19 m3 is at an elevation of + 140,00m to + 148,00m. The results of the water balance calculations indicate that the volume of 162.636,19 m3 can meet the need of irrigation water when the river flow shortage. Development Embung Tamanrejo be making buildings with construction masonry spillway and dam body using land fill. Embung planned height of 11 m, with a base elevation at the dam crest elevation +140,00 m and the top reservoir at +151,00 m. Dam crest width 5,00 m, the upstream slope of 1:3 and the downstream slope of 1: 2,25. In planning Embung Tamanrejo used Concrete drop Open Ogee type (overflow spillway) with a width of 25 m, a length of 13 m and a peak elevation at +148,00 m, using an megrim USBR Type III with a length of 5,00 m.Plan implementation time is 24 weeks with work plan budget of RP.6.258.700.000,00 ( Six Billion Two Hundred Fiffty Eigth Million Seven Hundred Thousand Rupiah). Conclusion with built small dam can overcome the shortage of irrigation water